Assessment of Soil Liquefaction Potential Based on SPT Values at Some Ground Profiles in the North Central Coast of Vietnam - Nu, Nguyen Thi; Duong, Nguyen Thanh; Son, Bui Truong (Iraqi Journal of Science, 2021)
The North Central Coast of Vietnam has a wide distribution of loose sand which is often exposed on the surface. The thickness changes from a few meters to over ten meters. This sand with the loose state can be sensitive to the dynamic loads, such as earthquakes, traffic load, or machine foundations. It can be liquefied under these loadings, which might destroy the ground and buildings. The Standard Penetration Test (SPT) is widely used in engineering practice and its values can be useful for the assessment of soil liquefaction potential. Thus, this article presents some ground profiles in some sites in the North Central Coast of Vietnam and determines the liquefaction potential of sand based on SPT and using three parameters, including the Factor of Safety against Liquefaction (FSLIQ), Liquefaction Potential Index (LPI), and Liquefaction Severity Number (LSN). The research results show that the FSLIQ, LPI, and LSN values depend on the depth of sand samples and the SPT values. In this study, the sand distributed from 2.0 to 18.0m with (N1)60cs value of less than 20 has high liquefaction potential with FSLIQ<1, LPI is often higher than 0.73, and LSN is often higher than 10. The results also show that many soil profiles have high liquefaction potential. These results should be considered for construction activities in this area.